2018
DOI: 10.1002/hpm.2530
|View full text |Cite
|
Sign up to set email alerts
|

Social health insurance in Nepal: A health system departure toward the universal health coverage

Abstract: The World Health Organization has identified universal health coverage (UHC) as a key approach in reducing equity gaps in a country, and the social health insurance (SHI) has been recommended as an important strategy toward it. This article aims to analyze the design, expected benefits and challenges of realizing the goals of UHC through the recently launched SHI in Nepal. On top of the earlier free health-care policy and several other vertical schemes, the SHI scheme was implemented in 2016 and has reached po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 7 publications
0
38
0
Order By: Relevance
“…For addressing the financial constraint in health services, Nepal's Government implemented the Social Health Insurance Program (SHIP) in 2016. However, the program has been facing many challenges and only small portions of the population are enrolled under this scheme [13,14]. Despite the fact that research on CHE has been substantially studied around the world, very few research papers have been published in the context of Nepal.…”
mentioning
confidence: 99%
“…For addressing the financial constraint in health services, Nepal's Government implemented the Social Health Insurance Program (SHIP) in 2016. However, the program has been facing many challenges and only small portions of the population are enrolled under this scheme [13,14]. Despite the fact that research on CHE has been substantially studied around the world, very few research papers have been published in the context of Nepal.…”
mentioning
confidence: 99%
“…interventions in countries such as Nepal [82,90], Ugunda [117,118] Rwanda [75], Tanzania [50,77], Ethiopia [119], Afghanistan [62] and…”
Section: Discussionmentioning
confidence: 99%
“…Considering the economic conditions of countries, the results of the present study show that most of the interventions have performed in the eld of nancing or nancial protection functions. Thus, most interventions in these countries have focused on the insurance system and targeted the poor people or speci c groups of society [67,75,78,[80][81][82]120]. Also one of the issues that mostly reformed by countries is the payment and premium systems [60,65,99,121].…”
Section: Discussionmentioning
confidence: 99%
“…The government pays hospital a xed amount for providing haemodialysis and transplant service for the destitute through its impoverishment citizen fund established in 2016 [19,31]. However, in the absence of renal registry and fully viable health insurance system to cover expenses associated with the treatment, patients with ESRD face a major setback in living a quality life [31,37].Importantly, the government subsidy through the impoverished citizen fund does not cover all treatment expenses and moreover, there is a low enrollment and limited ceiling in bene t package (NPR 100,000) in health insurance [38]. In our study, even after transplant, QOL in environment domain was found comparatively lower than other domains in renal transplant.…”
Section: Discussionmentioning
confidence: 99%